Childhood prevalence of achondroplasia in New South Wales and the Australian Capital Territory, Australia. Issue 5 (27th February 2021) - Tofts, Louise; Armstrong, Jennifer; Pacey, Verity
Abstract: The aim of this study was to estimate the childhood prevalence of achondroplasia, trends over time in birth prevalence, and age at diagnosis in Australia. Children born between 1990 and 2019 with a clinical and radiological and/or molecular diagnosis of achondroplasia were identified from a tertiary hospital servicing New South Wales (NSW) and the Australian Capital Territory (ACT) and compared with population data from the Australian Bureau of Statistics. Childhood prevalence of achondroplasia, based on children ≤19 years of age and resident in NSW/ACT on June 30, 2019 ( n = 109), was 5.2 per 100, 000. A total of 127 individuals with achondroplasia were born in 1990–2019 in NSW/ACT. Birth prevalence rates increased across birth decades, from 3.3 per 100, 000 live births in 1990–1999 to 5.3 per 100, 000 in 2010–2019 ( p < 0.0001). Median age at diagnosis decreased to 17 days in 2010–2019 compared with 30 days in 1990–1999 ( p = 0.035), although the overall decreasing trend across consecutive decades did not reach statistical significance. This is the first study to show a rising birth prevalence rate for achondroplasia in Australia with a concurrent decreasing age at diagnosis, both of which were statistically significant after 2 decades.